Education in China and the World Achievements and Contemporary Issues - Niancai, Liu; Zhuolin, Feng; Qi, Wang (Springer Nature, 2024)
This open access book provides a comprehensive overview of education in China, covering 12 critical topics including basic education, higher education, professional education, STEM (Science, Technology, Engineering, and Mathematics) education, mental health education, and international education and excellence initiatives. Drawing from current research, theoretical literature, and real-life stories, this book examines the developmental trajectories, achievements, and best practices in the above-mentioned topics, to reflect realities of education transformation in China. It also incorporates a global comparison of key indicators to explore strengths of and gaps in Chinese education with its global counterparts. Setting its context in an ever-changing world, this book intends to explore conceptual support to develop "a modern education system with Chinese features and world standards", to provide implications for further developing quality education in all sectors, and to promote understanding and inspire critical discussion on education development in China and around the world. This book serves as a valuable resource for students, scholars, and policy makers in the field of education studies, as well as for the general public who are interested in Chinese education.